Multipotent precursors in the anterior and hippocampal subventricular zone display similar transcription factor signatures but their proliferation and maintenance are differentially regulated - Carrillo García, Carmen; Suh, Yongjoon; Obernier, Kirsten; Hölzl-Wenig, Gabriele; Mandl, Claudia; Ciccolini, Francesca (Molecular and cellular neuroscience, 2010)
Precursors within the subventricular zone (SVZ) exhibit regional variations in the expression of transcription factors important for the regulation of their proliferation and differentiation. In the anterior SVZ (aSVZ) the homeobox transcription factor distalless (Dlx)2 modulates both processes by promoting neural stem cell (NSC) activation as well as neurogenesis. Activated NSCs and transit-amplifying precursors (TAPs) in the aSVZ both express high levels of epidermal growth factor receptor (EGFR(high)) and form clones in response to exogenous EGF. EGF-responsive cells are also present in the hippocampal subependyma (hSVZ). However, it is not clear whether they represent NSCs or TAPs and whether their proliferation and differentiation are regulated as in the aSVZ. Here we have purified EGFR(high) cells from both the aSVZ and hSVZ at different ages. When isolated from perinatal tissue both populations were enriched in multipotent clonogenic precursors, which generated GABAergic neurons. Although they differed in absolute expression levels, activated NSCs and TAPs in both regions displayed similar signatures of transcription factor expression. However, activated NSCs were less frequent in the hSVZ than in the aSVZ. Furthermore, increasing age had a greater inhibitory effect on NSC proliferation in the hSVZ than in the aSVZ. This suggests that NSC activation is differentially regulated in the two regions. Consistent with this hypothesis, we found that in hippocampal precursors Dlx2 promoted neurogenesis but not NSC activation. Thus, most clonogenic EGFR(high) precursors in the hSVZ represent TAPs and NSC proliferation in the aSVZ and hSVZ is regulated by different mechanisms.
Gesehen am 25.01.2023